Resiliency Factors that Protect against Post-Deployment Drug Use among Male US Army Reserve and National Guard Soldiers - Hoopsick, Rachel A. (Drug Alcohol Depend, 2019)
BACKGROUND: Service members who have been deployed are at risk for substance use, especially Reserve/Guard troops. However, it is unclear what modifiable factors protect against substance use in this at-risk population. Our objective was to examine the effects of pre-, peri-, and post-deployment resiliency factors on post-deployment drug use. METHODS: Data were drawn from Operation: SAFETY (Soldiers and Families Excelling Through the Years), an ongoing study examining the health of US Army Reserve/National Guard (USAR/NG) soldiers. This sample consisted of male USAR/NG soldiers with at least one combat deployment (N = 228). At baseline, we assessed the following as potential protective factors: deployment preparation, unit support and support from family/friends during soldiers’ most recent deployment, and marital satisfaction. We examined the relations between each of these resiliency factors with drug use at the first follow-up assessment using the NIDA modified ASSIST 2.0. RESULTS: Greater unit support (AOR = 0.56, 95% CI: 0.34, 0.92; p < 0.05) and support from family/friends during deployment (AOR = 0.64, 95% CI: 0.43, 0.96; p < 0.05) were associated with lower odds of drug use, controlling for age, rank, years of military service, combat exposure, traumatic brain injury, time since last deployment, and baseline drug use. Deployment preparation and marital satisfaction were not associated with drug use (ps > 0.05). CONCLUSIONS: Social support provided to soldiers during deployment, either by his unit or his family/friends, showed evidence of protection against post-deployment drug use. In addition to existing post-deployment efforts, we recommend interventions that facilitate stronger interpersonal relationships during deployment.